Conflicted and confused? Health harming industries and research funding in leading UK universities. (27th July 2021) - Collin, Jeff; Wright, Alex; Hill, Sarah; Smith, Kat
Abstract : Jeff Collin and colleagues review how the UK's leading universities deal with research funding from health harming industries and call for more effective governance of conflicts of interest